2005
DOI: 10.1093/ps/84.11.1774
|View full text |Cite
|
Sign up to set email alerts
|

Effects of extended storage on egg quality factors

Abstract: Eggs were collected from a single inline processing facility weekly for 3 wk (replicates). The eggs were stored at 4 degrees C and 80% RH. Sampling began the day after collection and continued each week for 10 wk. During analysis, 24 eggs were examined for egg weight, albumen height, Haugh units (HU), shell strength, and vitelline membrane strength for each replicate. Egg weight decreased (P < 0.0001) from approximately 61 to 57 g after 10 wk of storage. Eggs from the second replicate were significantly (P < 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
87
1
20

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(122 citation statements)
references
References 18 publications
14
87
1
20
Order By: Relevance
“…Albumen height and HU values tend to decrease (Figure 1) during storage, which concurs with the finding of others (Caudill et al, 2010;Musgrove, 2005).…”
Section: Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…Albumen height and HU values tend to decrease (Figure 1) during storage, which concurs with the finding of others (Caudill et al, 2010;Musgrove, 2005).…”
Section: Methodssupporting
confidence: 91%
“…During 9 week storage, only Albumen height values (5.5 to 5.8 mm) for different housing systems similar to our refrigerated values was also reported Karcher;Abdo, 2014). Another research showed that albumen height decreased from 7.05 to 4.85 mm comparing the 1 st and 10 th week of extended cold storage Musgrove, 2005). In our work, HU decreased significantly when eggs remained at room temperature (average temperature), especially after the 2 nd week of storage.…”
Section: Summer Season and Different Storage Temperaturessupporting
confidence: 85%
“…Among these factors, storage time and temperature are the major factors affecting egg quality (Silversides and Scott, 2001;Jones and Musgrove, 2005;Samli et al, 2005;Jin et al, 2011;Shin et al, 2012). Albumen height and HU decrease during storage, and albumen quality gradually decreases with increasing temperature.…”
Section: Introductionmentioning
confidence: 99%
“…However, it then remained stable for up to 42 days at both temperatures. Jones and Musgrove (2005) demonstrated that the eggshell strength remains unchanged for 10 weeks at 4 °C. These results corroborate the assumptions of Vadehra et al (1970) andDe Reu et al (2006b) on the absence of a relationship between eggshell quality and thickness and the level of bacterial trans-shell penetration.…”
Section: Effect On Cuticle and Eggshell Integritymentioning
confidence: 99%
“…After laying, the strength of the vitelline membrane decreases during storage owing to the degradation of its structural integrity and to the increase in the egg yolk volume (Fromm, 1964;Back et al, 1982;Kirunda and McKee, 2000;Chen et al, 2005;Jones and Musgrove, 2005). If the membrane degrades, components of the yolk can diffuse into the albumen, resulting in a dramatic decrease of the antimicrobial defences of the egg albumen.…”
Section: Effect On Vitelline Membrane Integritymentioning
confidence: 99%